Upaya Meningkatkan Motivasi dan Hasil Belajar Siswa Pada Mata Pelajaran IPA Materi Struktur Akar Dengan Menggunakan Metode Demonstrasi dan Media Nyata Pada Kelas IV SDN 7 Bungtiang Tahun Pelajaran 2018/2019 - Hakim, Abdul Azizul (khatulistiwa, 2020)
The use of demonstration methods and real media in learning science root structure material can increase the motivation of fourth-grade students at SDN 7 Bungtiang, East Lombok Regency. This can be seen in the first cycle with the level of student statements, namely strongly agree (85%), agree (20%) and statements disagree and strongly disagree (0%) which are classified as active, while in cycle II the level of student statements is very agreed (95%), agree (5%) and statements disagree and strongly disagree (0%) which are classified as very active. This shows the enthusiasm and motivation to learn continues to increase by using demonstration methods and real media. The use of demonstration methods and real media in science learning of Root Structure Materials can improve the learning outcomes of fourth-grade students at SDN 7 Bungtiang, East Lombok Regency with the classical mastery formula. This can be seen from the acquisition of student learning completeness in the first cycle of 56.67% and in the second cycle of 83.67%. According to the curriculum, it is said to be classically complete if it gets a score of 80%. So completeness occurs in cycle II With the use of demonstration methods and real media students' learning motivation increased as seen from the results of the student motivation questionnaire in the first cycle, namely strongly agree (85%), and agree (20%) and in the second cycle strongly agree (95%) and agree (5%) while the increase in student motivation in each cycle of strongly agree (10%), agree (15%)